Analisis Intervensi Niat Menggunakan Financial Technology Dan Keputusan Pengguna Jasa - Milliani Susantri; Meisa Fitri Nasution; Pristiyono (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The purpose of this study is to analyze from a different angle by placing the views ofrespondents through variables and indicators of the perception of the convenience of fintechand the perception of the benefits of fintech on the level of fintech. This study took 150samples of the population of Labuhanbatu Regency who lives in the city of Rantauprapat. Thedata collection method is in the form of primary data with the Google Form application inwhich there is a Likert scale. Determination Sampling using simple random sampling. Thedata analysis technique uses descriptive statistics and data analysis uses partial least squares(PLS) to obtain latent variables for prediction purposes with the stages of analysis of theouter model, inner model, and hypothesis testing. The results show that the perception of theconvenience of fintech has a direct effect on the intention to use fintech, the perception of thebenefits of fintech has a direct effect on the intention to use fintech, the perception of theconvenience of fintech has a direct effect on user decisions, the perception of the benefits offintech has no direct effect on user decisions and the intention to use fintech has a direct effecton decisions. user.